Organising forestry research to meet the challenges of the information age - Byron, R.N.; Sayer, Jeffrey A. (1999)
This paper examines the needs for forest science for the 21st century and ways of organising research to meet them. The world of the 21st century will be one of knowledge-based societies and globalised economies. The need for global stewardship of the environmental and social values of forests is finally being accepted. Yet pressures for economic efficiency and competitiveness are reducing the resources available to state forest agencies. Many countries are transferring management of production forestry to the private sector. Emerging technologies are greatly enhancing our ability to assess and monitor forest attributes, to process and disseminate information as well as to grow trees faster and to more narrow industrial specifications. Such changes will affect how forest science is organised, creating new demands for and new suppliers of, research. Funding responsibilities will be redistributed between the private and public sectors, The private sector can take over conventional forestry research on productivity enhancement, but it is unclear who will fund research supporting the public values of forests at the local, national and global levels.